Low blood pressure and guideline-directed medical therapy in patients with heart failure with reduced ejection fraction. (1st January 2023) - Izumi, Keiichi; Kohno, Takashi; Goda, Ayumi; Takeuchi, Shinsuke; Shiraishi, Yasuyuki; Saji, Mike; Nagatomo, Yuji; Tanaka, Toshikazu D.; Takei, Makoto; Nakano, Shintaro; Soejima, Kyoko; Kohsaka, Shun; et al.
Abstract: Background: Patients with heart failure (HF) presenting with low blood pressure (BP) have been underrepresented in large-scale clinical trials. We investigated the characteristics and implementation of conventional guideline-directed medical therapy (GDMT; renin-angiotensin system inhibitors and β-blockers) in patients with low BP hospitalized for HF with systolic dysfunction. Methods: Conventional GDMT was evaluated by discharge BP among 2043 consecutive patients with HF and left ventricular ejection fraction (LVEF) < 50% in the WET-HF registry. Among the 708 (34.7%) patients with lower discharge BP (≤ 100 mmHg; the lower tertiles), exploratory subgroups included patients with previous HF hospitalization, inotrope use, New York Heart Association (NYHA) III–IV class, and lower estimated glomerular filtration rate (eGFR) and LVEF (lower than median value). We evaluated the risk-adjusted association between GDMT implementation and 2-year adverse events (all-cause mortality or HF rehospitalization). Results: Among the 2043 patients (age 74 [63–82] years), the median systolic BP was 108 (98–120) mmHg. Among patients with lower BP, GDMT prescription rate was 62.7%, and GDMT use was associated with decreased adverse events (HR:0.74, 95%CI:0.58–0.94). GDMT prescription rates were lower among higher-NYHA class and lower-eGFR subgroups compared with their reference subgroups, and directionally similar outcomes were noted in all subgroups (favoring GDMT use); however, this association was somewhat attenuated in the lower-eGFR group (HR:0.87, 95%CI:0.64–1.17). Conclusions: Conventional GDMT use was associated with decreased adverse outcomes in most patients with HF compounded by systolic dysfunction and low BP, albeit caution is warranted in patients with renal dysfunction. Highlights: ≈60% of HF patients with systolic dysfunction and low BP received conventional GDMT. Low BP was associated with worse long-term clinical outcomes. Conventional GDMT use was associated with better clinical outcomes in low BP group. The favorable prognostic effect of GDMT was consistent across all high-risk subgroups. This association was somewhat attenuated in the lower-eGFR subgroup.